POSISI EKSPOR PRODUK OLAHAN PERTANIAN INDONESIA DI NEGARA ASEAN - Endang Mei Wulandari; Suardi Tarumun; Ermi Tety (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to analyze the position of processed agricultural products exports of Indonesia in ASEAN countries. The data used in this research is secondary data that is in the form of time series data for 10 years that is the2005-2014 in the year can be from various sources such as the United Nations Commodity Trade Statistics Database, World Trade Organization, the Ministry of Trade etc. The analysis of the data used in this research is a descriptive analysis, that analysis that describes the position of the export of processed agricultural product Indonesia in ASEAN countries. Results of the study concluded that the export of processed agricultural products position ASEAN countries highest occupied by Indonesia with the export value reaching US21.28 billion in 2014. While the next position occupied by Malaysia, Thailand, Viet Nam, Singapore and the Philippines.Keywords: Processed Agricultural Products, Export, Export Value Position